Testes de vigor e a relação com a emergência de plântulas de soja a campo - Wendt, Letícia (2015)
One of the priorities of the seed companies is to reduce the time to decide on the fate of lots and vigor tests, meet these objectives, with fast and accurate results. Given the above, this study aimed to identify the vigor tests that better predict the establishment of field soybean seedlings. We evaluate six seed lots of cultivar CD 2737 RR, with four replications, implanted in the laboratory in a completely randomized design and in the field in a randomized block design. The variables analyzed were [CO2], vigor index - SVIS® (Seed Vigor Imaging System), accelerated aging (EA), tetrazolium (TZ), electrical conductivity (EC), emergency field in seedlings (EP) and speed index emergency (IVE). Data were submitted to analysis of variance and after, the Lilliefors normality test, and the averages grouped to the level of 5% probability by Scott- Knott test. The performance in soybean field is determined by the tetrazolium test, accelerated aging, electrical conductivity and analysis of CO2 concentration